Team governance: empowerment or hierarchical control - Guido Friebel; Wendelin Schnedler (Institute for the Study of Labor (IZA), 2007)
We investigate a team setting in which workers have different degrees of commitment to the outcome of their work. We show that if there are complementarities in production and if the team manager has some information about team members, interventions that the manager undertakes in order to assure certain efforts may have destructive effects: they can distort the way workers perceive their fellow workers and they may also lead to a reduction of effort by those workers that care most about output. Moreover, interventions may hinder the development of a cooperative organizational culture in which workers trust each other. Thus, our framework provides some first insights into the costs and benefits of interventions in teams. It identifies that team governance is driven by the importance of tasks that cannot be monitored. The more important these tasks, the more likely it is that teams are empowered.
Keywords: 330; Team work; incentives; informed principal; intrinsic motivation; Gruppenarbeit; Leistungsmotivation; Agency Theory; Leistungskontrolle; Leistungsanreiz; Vertrauen; Theorie